Neisseria gonorrhoeae: An Unexpected Cause of Polyarthritis and Meningitis. (April 2021) - Mathew, Reshmi; Chahin, Michael; Isache, Carmen
Neisseria gonorrhoeae, a gram-negative coccus, is a major cause of morbidity among sexually active individuals. Hematogenous spread of N gonorrhoeae from the initial site of infection is thought to occur in only 0.5% to 3% of infected patients. Disseminated gonococcal infections can rarely lead to serious sequelae, such as endocarditis or meningitis. In this article, we present a case that demonstrates a rare finding of disseminated gonococcal infection leading to N gonorrhoeae meningitis, complicated by hydrocephalus. The patient in this case initially presented with intermittent polyarthralgias for two years and later developed a rash. Cultures from blood and joint aspirate were negative. Urine nucleic acid amplification test for N gonorrhoeae was also negative. He was initially started on steroids for what was believed at first to be an autoimmune polyarthritis. The patient later developed acute encephalopathy. Head imaging revealed hydrocephalus. Cerebrospinal fluid analysis was consistent with bacterial meningitis. Blood, joint, and mucosal membrane studies failed to isolate the causative organism, but his cerebrospinal fluid grew N gonorrhoeae . He was treated with high-dose intravenous ceftriaxone for two weeks with rapid improvement in his mental status and resolution of his joint pains and rash.